Application of a deep eutectic solvent to prepare nanocrystalline Ni and Ni/TiO2 coatings as electrocatalysts for the hydrogen evolution reaction. (20th September 2019) - Protsenko, V.S.; Bogdanov, D.A.; Korniy, S.A.; Kityk, A.A.; Baskevich, A.S.; Danilov, F.I.
Abstract: The paper reports the electrochemical deposition of nanocrystalline nickel and composite nickel-titania films as effective electrocatalysts for the hydrogen evolution reaction. To produce the composite Ni/TiO2 electrodeposits, a plating bath based on a deep eutectic solvent, a novel kind of ionic liquids, was used for the first time. The electrolyte contained ethaline (a eutectic mixture of choline chloride and ethylene glycol), 1 M NiCl2 ⋅6H2 O and the addition of extra water (3, 6, 9 mol dm −3 ). Titania dispersed phase was introduced into the electrolyte as nanopowder Degussa P 25 (0–10 g dm −3 ). It was shown that the introduction of extra water to the plating bath allowed appreciably increasing the content of TiO2 phase in the coating (from ca. 2 to 10 wt%). The effects of electrolysis conditions on the TiO2 content in the coatings, surface morphology and microstructure were determined. The results of voltammetry measurements showed that the Ni and composite Ni/TiO2 coatings electrodeposited from the plating electrolyte based on a deep eutectic solvent exhibit improved electrocatalytic properties towards the hydrogen evolution reaction as compared with deposits obtained from commonly used aqueous electrolytes. The mechanism of the hydrogen evolution reaction on the Ni and composite Ni/TiO2 coatings is a combination of Volmer-Heyrovsky reactions. The introduction of TiO2 particles into the nickel matrix results in the acceleration of the hydrogen evolution reaction. An improved catalytic activity of Ni/TiO2 composites towards the hydrogen evolution reaction can be associated with the presence of titanium-containing redox couples on the surface. Highlights: Ni and composite Ni/TiO2 films electrodeposited from deep eutectic solvent, ethaline. Extra H2 O ensures decreasing viscosity and increasing the content of TiO2 in coatings. DES-based electrolytes produce nanocrystalline electrocatalytic coatings. Ni/TiO2 composites show enhanced electrocatalytic activity towards the HER. Exchange current of the HER for Ni from DES is 100 times higher than from water bath.